Studies the effect of halloysite nanotubes on the mechanical and hot air ageing properties of nitrile-polyvinyl chloride rubber nano-composites. (2021) - Senthilvel, K.; Arul Jeya Kumar, A.; Seeman, M.; Ashok Kumar, I.; Prabu, B.
Abstract: In this work the effect of halloysite nanotubes (HNT) on the mechanical properties and thermo-oxidative ageing behaviour of Nitrile-Polyvinyl chloride rubber (NBR/PVC) nano-composites is investigated. NBR/PVC nano-composites containing 2, 4, and 6 phr of HNT were prepared by melt-blending on a twin roll mill. X-ray diffraction and Field emission scanning electron microscopy studies revealed formation of limited intercalated structures in NBR/PVC matrix. Fourier transform infrared spectroscopy studies confirmed the formation of hydrogen bonding between NBR/PVC and HNT. Improved interaction between NBR/PVC and HNT increased the tensile strength, elongation at break and tensile modulus by 34%, 22%, and 23% respectively and improved the hardness and compression set. Hot air ageing tests revealed that all the NBR/PVC nano composites demonstrated excellent retention of properties compared with that of conventional composites.